2022
DOI: 10.1101/2022.09.01.506194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid intralacustrine evolution of an invasive pelagic three-spined stickleback (Gasterosteus aculeatus) ecotype in Lake Constance

Abstract: The rapid invasion of the pelagic zone in Lake Constance by three-spined sticklebacks (Gasterosteus aculeatus) since 2012 and their subsequent drastic population growth has had stark ecosystem-wide effects, such as food-web shifts and declines in native biodiversity, including commercially important fish species. Yet, the origin of this invasive pelagic ecotype remains unclear. This study aims to determine if the pelagic ecotype arose in situ from the existing littoral population or following external colonisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 134 publications
(176 reference statements)
1
4
0
Order By: Relevance
“…However, given that all sticklebacks spawn in the same shallow waters of ULC (Gugele et al, 2020), the mechanism of separation (e.g., mate choice) is not known at this stage. Nevertheless, our results together with the genetic evidence by Dahms et al (2022) point to a rare case of littoral‐pelagic ecotype divergence, with food selectivity as an important factor.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…However, given that all sticklebacks spawn in the same shallow waters of ULC (Gugele et al, 2020), the mechanism of separation (e.g., mate choice) is not known at this stage. Nevertheless, our results together with the genetic evidence by Dahms et al (2022) point to a rare case of littoral‐pelagic ecotype divergence, with food selectivity as an important factor.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, the hypothesis arose that a benthic‐pelagic species pair in ULC with reduced genetic exchange in this system exists (cf. Dahms et al, 2022). Our data support this hypothesis, highlighting differences in the diets and fatty acid profiles of littoral and pelagic groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…during whitefish larvae stocking (Roch et al 2018). Due to rapid evolution, sticklebacks may now diverge into groups occupying littoral, pelagic or profundal habitats (Hudson et al 2021), albeit, up to now only subtle genetic differences between individuals occupying different habitats were observed (Dahms et al 2022). Our study showed that the pelagic sticklebacks have already specialised in feeding on zooplankton.…”
Section: The Effects Of Sticklebacks On Zooplankton and Planktivorous...mentioning
confidence: 68%